Communication in chest diseases; cohort analysis on medical faculty students taking communication course in health (Annals of Medical Research, 2021)
Aim: The aim of this course was to evaluate the effectiveness of the 'Communication in Health' course given at the Faculty of Medicine and the effect of taking this course on patient communication and exam success in clinical education processes, in particular for chest diseases internship in medical students. Materials and Methods: In this cohort-designed study, 102 volunteer students who received medical communication lessons in the third grade and Chest Diseases internship in the fourth grade in medical school, were evaluated. The Communication Skills Scale (CSS) was applied as a pre-and post-test in health communication lesson and written exam, practical exam, and patient presentation for clinical internship in chest diseases. Results: The mean pre-test score for communication lessons was found to be 58.77 ± 8.09 and the mean post-test score was found to be 94,46±5,40 in the students who had a mean age of 21.35 ± 1.56 years. While the mean CSS pre-test score was found to be 94.37 ± 9.42, the mean post-test score was found to be 105.53 ± 8.02. It was found that there was an increase in the CSS scores and in the subscale scores of communication principles and basic skills, effective listening and non-verbal communication, self-expression, and willingness to communicate in the students who received "communication in health" lesson, and there was a statistically significant difference. In addition, we found a statistically significant positive correlation between the students' chest disease course grades and the total scores of the CSS scale.Conclusion: It is consider that there is an increase in the communication skills of medical students who take "communication in health" lessons, and this increase also contributes to the clinical education processes specifically in terms of chest diseases internship. Communication skills and drama lessons should be given in medical education.
Keywords: Chest Diseases; communication skill; medical education; medical students